URGENSI PELIBATAN GENERASI MUDA DALAM PENGAWASAN PARTISIPATIF UNTUK PEMILU SERENTAK TAHUN 2024 YANG DEMOKRATIS - Nur Hayati, Neni (Jurnal Keadilan Pemilu, 2021)
The 2024 simultaneous elections that unite the elections for the president and vice president, House of Representatives (DPR), Regional House of Representatives (DPD), Provincial and Regency/City Representatives Council (DPRD) and the elections for the Governor and Deputy Governor, the Regent and Deputy Regent, the Mayor and Deputy Mayor, face formidable challenges. In order to ensure the integrity of elections, this paper aims to investigate more comprehensively the involvement of the youth in participatory supervision. The research employs a qualitative approach based on a literature study to investigate more deeply related issues that arise in the context of participatory supervision, including the obstacles and challenges faced, the urgency of involving youth in overseeing the electoral process, and the efforts in developing democracy and being involved in the policy-making process in accordance with the applicable laws and regulations, as well as realizing synergy and collaboration between stakeholders related to cooperating with youth as the main element in realizing people's sovereignty.